Students and Orang Utan Conservation: High School Students’ Perceptions of Orang Utan Sanctuary Establishment in Balikpapan Bay, East Kalimantan, Indonesia - Tri Sayektiningsih; Ulfah Karmila Sari; Ishak Yassir; Amir Ma'ruf (Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Makassar, 2020)
The role of young generations including students was crucial in orang utan conservation. They are not only agent of change, but they are also capable of distinguishing attitudes which are able to influence policy in the future. The purpose of this study was to examine high school students’ perceptions of establishment of the orang utan sanctuary in Balikpapan Bay. We used quantitative and qualitative approaches for data collection with students on the grade of XII as respondent. Data was analyzed descriptively and quantitatively. The findings showed that students had good perceptions towards unreleased orang utan conservation. They agreed that the orang utan sanctuary should be established. Students also had positive perceptions relating to the positive impacts of orang utan sanctuary on the village and environment. However, students had neutral perceptions towards negative impacts of orang utan sanctuary. There were no differences between male and female students’ perceptions towards the establishment of orang utan sanctuary. Conversely, male and female students’ perceptions in regards with the impacts of orang utan sanctuary on the village and environment were differed.